Terrorism and the Socio-Economic Development of Nigeria - Obi , Edward Nku (Interdisciplinary Journal Of Lifelong Learning, 2025)
This study examines how terrorism has created an atmosphere of fear through the various attacks on people, and infrastructure such as airport; seaport, railway etc. which had stunted the development of the nations’ economy. However, the study adopted the survey research design method with the use of a simple random sampling technique to select respondents. The instrument for data collection was a structured questionnaire on a five (5) point scale of strongly agreed, agreed, strongly disagreed, disagreed and undecided; one hundred and fifty (150) questionnaires were administered to the respondents. The descriptive statistics such as frequency counts and percentages were used for the analysis. The findings revealed that terrorist activities had stunted the socio-economic development of the country to the extent that investors have relocated to other parts of the countries for fear of being kidnapped, destruction of their investments and other valuable assets. Hence, the study recommends that the government should engage the teeming population with jobs as this would reduce the level of poverty and unemployment that is occasioned by terrorist groups. Also, the government should put in place adequate measures to protect and safeguard the territorial integrity of the State as this will bring about a secured environment, and security of the people. Lastly, government should create an avenue for transparent discussions and negotiations with the terrorists to embrace an alternative dispute resolution and accept amnesty offered by the government.